Combination of Rank Sum and Multi Attribute Utility Theory in Determining the Best Receptionist Performance - Arshad, Muhammad Waqas; Setiawansyah, Setiawansyah; Mesran (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
As the frontline of the service industry, a receptionist's performance not only reflects his professionalism, but also affects the first impression and overall customer experience. Problems in assessing the performance of a receptionist can include several things, namely difficulty measuring the quality of social interactions objectively, performance appraisals often focus more on administrative tasks, lack of understanding of the receptionist's role as a liaison between the company and customers, difficulty in assessing intangible aspects such as friendliness, patience, or the ability to respond to changing customer needs quickly and efficiently. The combination of rank sum weighting methods and Multi-Attribute Utility Theory (MAUT) can result in a more holistic and robust approach to decision making. In this approach, the rank sum weighting method can be used to get an initial picture of the relative preferences of various alternatives, while MAUT can be used to dig deeper into those preferences and account for complex factors such as attribute weights and utility values. By combining these two methods, decision makers can gain a deeper understanding of their preferences, while still maintaining openness to multiple perspectives and information. The results of the ranking of the best cashier performance the 1st best cashier with a value of 0.574 obtained by Zulaikah, the 2nd best cashier with a value of 0.473 obtained by Arini, and the 3rd best cashier with a value of 0.337 obtained by Lilik Karlina.